Personality, ability, marriage and the gender wage gap: Evidence from Germany - Matthias Collischon (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2016)
This study investigates the interplay between personality traits, cognitive ability, marriage and the gender wage gap for West Germany by using data from the GSOEP. The findings indicate that personality traits in the form of the five factors of personality account for 11% of the total gender wage gap, while ability does not have an effect on the wage differential. There also seems to be a strong and significant marriage premium for men. Comparing unmarried men to unmarried women, a gender wage gap of 4.7 log points remains. This study also takes selection into the labor market into account, which hardly changes the results.
Keywords: J16; J31; 330; gender wage gap; big five; Germany